Influence of School Resource Management Practices on Teacher Performance and Student Academic Achievement in Public Secondary Schools in Oyo State, Nigeria - SALAMI, Muideen Oladeji; ADEWUYI, Habeeb Omoponle; ONI, Lawrence Adedayo (Center for Risk Management & Sustainability and RSF Press, 2026)
This study examines the influence of school resource management on teacher performance in public secondary schools in Oyo State, Nigeria. Inadequate resource allocation undermines teacher effectiveness, contributing to poor student outcomes in examinations. The research investigates four resource management practices, namely allocation of instructional materials, financial management, infrastructure maintenance, and professional development resources, using a quantitative descriptive survey design. Data were gathered from 906 teachers across 97 schools, selected through two-stage random sampling, using a resource management survey and a teacher performance questionnaire. Multiple regression analyses revealed that these practices collectively explain 69 percent of the variance in teacher performance, R2 equals 0.690, p less than 0.001, with professional development resources as the strongest predictor, beta equals 0.33, p less than 0.001. Allocation of instructional materials, beta equals 0.26, p less than 0.001, and financial management, beta equals 0.20, p equals 0.001, significantly enhance performance, while infrastructure maintenance shows a weaker, non-significant effect, beta equals 0.11, p equals 0.12. Teacher performance strongly predicts student academic achievement, beta equals 0.41, p less than 0.001, R2 equals 0.68, highlighting its role in improving examination results. These findings emphasise the need for effective resource management to support teachers. Recommendations include prioritising professional development funding, ensuring equitable material allocation, and strengthening financial oversight through transparent budgeting. The study provides evidence to guide policy reforms, addressing Oyo State’s educational challenges and supporting Nigeria’s universal basic education goals.